List of Meetings (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1932)
Trans No. Place Date Vol. 1. Wilkes-Barre, Pa. May, '71 1 2. Bethlehem, Pa. Aug., '71 1 3. Troy, N. Nov., '71 1 4. Philadelphia, Pa. Feb., '72.. 1 5. New York, N. Y. May, '72 1 6. Pittsburgh, Pa. Oct., '72 1 7. Boston, Mass. Feb., '73 1 8. Philadelphia, Pa. May, '73 2 9. Easton, Pa. Oct., '73 2 10. New York N. Y. Feb., '74 2 11. St. Louis, Mo. May, '74 3 12. Hazleton, Pa. Oct., '74.. 3 13. New Haven, Conn. Feb., '75 3 14. Dover, N. J. May, '75 4 15. Cleveland, Ohio Oct., '75 4 16. Washington, D. C. Feb., '76 4 17. Philadelphia, Pa. June, '76 5 18. Philadelphia, Pa. Oct., '76 5